Differential diagnosis of hematogenous osteomyelitis and malignant bone tumors - A. N. Tkachenko; O. F. Nur; A. A. Korneenkov; L. E. Sharova; I. E. Itskovich; I. I. Kushnirchuk; A. Yu. Cherkasov (Вестник хирургии имени И.И. Грекова)
The objective of the study was to develop a mathematical model of differential diagnosis of hematogenous osteomyelitis and malignant bone tumor.Material and methods. In this research we performed a retrospective analysis of the data on 127 patients with differential diagnosis between hematogenous osteomyelitis and malignant bone tumors. Retrospective validity indicators: sensitivity (Se) – 53.12 % (42.66–63.39 %), specificity (Sp) – 70.97 % (51.96–85.78 %). Data on 96 patients with subsequently diagnosed hematogenous osteomyelitis was compared with data on 31 patients with morphologically confirmed malignant bone neoplasms. In the research we.Results. The database was created based on studying the data of the retrospective group. It became the basis for the development of a mathematical model for the differential diagnosis of hematogenous osteomyelitis and malignant bone tumors. 13 prognostic criteria were identified, each of which is quantified. These criteria included the age of the patient, sex, the data on concomitant pathology, information about the localization of the pathological process, the indices of some laboratory studies, etc. An algorithm for the differential diagnosis of hematogenous.Conclusion. Our differential diagnostic model was tested in the prospective study (63 cases). Indicators of the validity of the test was: Sensitivity – 83.05 %, Specificity (Sp) – 86.67 %. Positive Predictive Value (PPV) was 96.08 %, Negative Predictive Value (NPV) – 56.52 %, Accuracy – 83.78 %, which allowed to shorten the time of examination and send patients to specialized hospitals.